“Factores psicosociales y su impacto en el desempeño de los trabajadores de las Cooperativas de Ahorro y Crédito del cantón La Maná, provincia de Cotopaxi, Año 2020”. - Enríquez Martínez, Selena Lizbeth (2021)
The research was carried out in the credit unions in La Maná. This sector has grown considerably in recent years and currently has 12 financial institutions, employing 87 people. The problem among these cooperatives was the lack of knowledge of the incidence of psychosocial factors on the work performance of the workers, and also the lack of research to answer this problem. The general objective was therefore to determine the incidence of psychosocial factors on workers' performance. The types of research used were: descriptive, bibliographic, field, correlational, and historical-logical, inductive, deductive, analytical and synthetic methods, supported by the interview technique applied to the 12 managers or representatives and the survey of the 87 workers of the credit institutions. The data from the surveys were processed using SPSS version 26 software, which allowed the following most significant relationships to be established: the relationship 1, job satisfaction that was linked to motivational factors by 0.511, which was considered a strong positive relationship, the relationship 2, job satisfaction in relation to workers' expectations presented a correlation of 0.604, considered a strong relationship. In conclusion, psychosocial factors do affect workers' job performance, due to several factors such as personal problems, work overload, fear of untimely dismissal, wage adjustments, inflexibility and inadequate synergy between workers. In view of the results obtained, a psychosocial risk prevention plan was designed, the proper implementation of which contributed to improving the work performance and quality of life of workers in the credit unions in La Maná.